Human blood plasma catalyses the degradation of Lycopodium plant sporoderm microcapsules - Fan, Teng-Fei (2019)
Plant sporoderm are among the most robust biomaterials in nature. We investigate the erosion of Lycopodium sporoderm microcapsules (SDMCs) triggered by human blood plasma. Dynamic image particle analysis (DIPA), field emission scanning electron microscopy (FESEM) and Fourier transform infrared (FTIR) spectroscopy demonstrate the degradation events, suggesting bulk erosion as the dominant mechanism for SDMCs fragmentation in human blood. These results should prove valuable in discerning the behaviour of SDMCs in potential biological applications.